Актуальность применения языковой модели LaMDA как инструмента образовательных технологий - Лагун, Е. А.; Железко, Б. А. (БНТУ, 2022)
This article presents an analysis of the possibility of introducing the Language Model for Dialogue Application (LaMDA) into the educational process of the Republic of Belarus. The advantages and disadvantages of this system are considered. The prospects for the development of the systems of innovative education with a rational approach to the introduction of new forms of educational technologies are shown.